Taṭbīq aṭ-Ṭarīqah al-Mu`addalah Fī Ta`līm Qawā`id al-Hamzah Li Tarqiyah Saiṭarah aṭ-Ṭālibāt `Alā Fahm Kitābah al-Hamzah (Dirāsah Tajrībiyah Li al-Marḥalah al-Mutawassiṭah Bi Ma`had Inṣāf al-Dīn): (تطبيق الطريقة المعدّلة في تعليم قواعد الهمزة لترقية سيطرة الطالبات على فهم كتابة الهمزة (دراسة تجريبية للمرحلة المتوسطة بمعهد إنصاف الدين - Yulia Safitri; Mukhlisah Mukhlisah (The Department of Arabic Language Education, Pascasarjana Universitas Islam Negeri Banda Aceh of UIN Ar-Raniry Banda Aceh, Aceh, Indonesia., 2020)
The research problem in this thesis is that many students of class two mistakenly write Hamzah, for example in the verb